Upaya Meningkatkan Keaktifan Belajar IPS melalui Model Pembelajaran Think-Pair-Share Siswa Kelas IX SMP Negeri 2 Wanasaba Semester II - Malhiah, Malhiah (Lembaga Yasin AlSys, 2022)
This study aims: To determine the increase in learning activeness in social studies subjects through the application of cooperative learning type Think Pair Share for Class IX-A students of SMP Negeri 2 Wanasaba in the 2021 /2022 academic year. This research is a classroom action research conducted in 2 cycles with three meetings per cycle with a total of 27 students consisting of 14 male students and 13 female students, as well as teachers as teachers. The results showed that: The results of the teacher's observations in the first cycle obtained the score in the first cycle was 40 or (71.43%), while the observation data in the second cycle obtained a score of 48 was 29 or (85.71%). This indicates that the teacher's success rate in learning is in the very good category. The results of the learning evaluation of students in social studies learning, it was found that the average score of students before the classroom action was carried out had an increase from the initial data value obtained by an average of 62,8, to 66,3. in the first cycle and to 83.8 in the second cycle with the completeness of learning obtained preliminary data. only (63%), became (76.00%), in cycle I and became (92,5%) in cycle II.